Persepsi Masyarakat Terhadap Penggunaan Pedestrian Sebagai Ruang Publik (Studi Kasus : Area Pedestrian Jalan Pelabuhan Ulee Lheue) - Nanda Yuli Elfizar; Zya Dyena Meutia; Fahmi Aulia; Zardan Araby (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2023)
Abstract. Public open space is a place that can fulfill a need that is functional. Public open space in the Ulee Lheue considered still lacks that this area requires special attention to well ordered. Researchers conducted research in the Ulee Lheue because this region is particularly at the area of pedestrian roads Ulee Lheue port there are still many obstacles. An area used as a pedestrian has been used for a trade for small street vendors located in that area. Researchers collected perception of the community for getting data on pedestrian Ulee Lheue in the area. This study in a qualitative approach case study and use the data collection techniques in a searching manner a literature review, observation, interview and documentation. This study also uses the data analysis descriptive heading for described the data obtained through research. The result showed that the pedestrian Ulee Lheue were succesful with proper facilities mand infrastructure. Ulee Lheue public space in an area used quite well. Many visitors do activities in the area of pedestrian street vendors. The use of the pedestrian by street vendors can interfere with the activity of the community especially the riding a motorcycle, so in the region every day deadlocked result of traders who use the pedestrian and the roads as a trading.